Your place or mine: transnational education and the locus of control - Ling, P.; Giridharan, Beena; Mazzolini, M.; Yeo, S.; Goerke, Veronica; Lueckenhausen, G. (Higher Education Research and Development Society of Australasia, Inc, 2013)
In transnational education the place – in both an organisational and a geographic sense – in which educational decisions are made impacts on the academics involved and on student learning. The subject of this paper is learning and accreditation that takes place outside a home university through offshore branch campuses. A case study of two Australian Universities with offshore campuses in Sarawak, Malaysia was undertaken. Policies and procedures were reviewed and an empirical study of the experiences of academics involved was conducted. The study focused on who makes decisions about curriculum content, learning and teaching activities, design and provision of educational resources, and the assessment of student work. Consequences of the organisational relationships for academics involved and for student learning are examined in this paper. On the basis of the study a high degree of local control is recommended, at least for units of study that have operated transnationally several times.